Deskripsi Kesulitan Belajar Siswa dalam Pembelajaran Tematik di Kelas V Sekolah Dasar Negeri 36 Pontianak Kota - Wulandhari Wulandhari; Kartono Kartono; Rio Pranata (Departement of Mathematics Education, 2023)
Learning difficulties are conditions under which students cannot learn as they should. By understanding the learning difficulties experienced by students, teachers can provide reasonable learning efforts according to the situation of students in class. This study aims to determine student learning difficulties in thematic learning, which then determines the causal factors and efforts to overcome student learning difficulties in Class V at SD Negeri 36 Pontianak Kota. The research method used was qualitative descriptive research. The data collection methods used in this study were observation, interviews, and documentation. The research steps used in the data analysis were data collection, data reduction, data presentation, and conclusion.Based on the results of the study, it was found that the learning difficulties experienced by the students were dyslexia (reading difficulties), dysgraphia (writing difficulties), dyscalculia (numeracy difficulties), underachievers (underachievement), and slow learners (slow learning). Internal and external factors influence students’ learning difficulties. Internal factors include psychological factors such as intelligence, learning attitudes, and learning motivation. External factors that come from outside the student's self, include learning methods and the family environment. The efforts made by the teacher to overcome student learning difficulties are to provide repeated exercises, use visual aids, and remedial material on material that has not been mastered.